" Princeza do Norte": contradições da modernidade em Diamantina (1889-1930) - Carolina Paulino Alcantara (2015)
This study arose from the need to understand how the ideals of modernity, circulating in the late 19th and early 20th century, were expressed in small towns, like Diamantina-MG, guiding speeches and promoting development strategies and local improvements. In the case of the Northern Town, it seeks to understand how its elites faced the dilemmas of urban and rural modernization that marked the period of the First Republic in Brazil. Therefore, more than draw up a systematic plan to promote economy and municipal policy, modernity in Diamantina was experienced as a speech, that is, a set of proposals drawn up with the intention of promoting local improvements, aiming at a more promising future for the region. This paper deals with projects/speeches of modernity in Diamantina in the First Republic, the main object being debates and disputes about the sanitation of the town and hinterland of Northern Minas region. The sources used are the Diamantina papers and minutes of meetings of the Municipality of Diamantina. The methodology for reading and analysis of this material was to consider forms of internal organization of the content, the groups responsible for the publication and the public to which it is intended. All material was analyzed according to the chosen problematic, privileging the speeches of modernity, sanitation, ideals of progress and civilization, representations of the town and the North of Minas Gerais, local political disputes, among others. The concept of social imaginary set the parameters necessary for understanding the role of editors of newspapers in shaping and disseminating the signs and modern elements as well as those associated with the hinterland. It was possible to identify that health issues also revealed the impasses of modernity in Diamantina, demonstrating that for Diamantina elites sanitation could be a facilitator for the achievement of progress and civilization. The review of the meanings of hinterland and its association with the North of Minas State confirmed that more than just meet the urban dilemmas, the Diamantina elites faced the problem of the town, by forging and inserting in the backcountry the image of the Northern Princess, an advanced center in backward hinterland. For this analysis the concept used was that of between-places. Thus, at the end of this study, it is expected that the reader know more about the practices, experiences, speeches and policy in Diamantina during the First Republic.